An Examination of Blood Lead Levels in Thai Nielloware Workers - Somsiri Decharat; Pornpimol Kongtip; Prapin Thampoophasiam; Anamai Thetkathuek (Elsevier, 2012)
Objectives: The objectives of this study were to determine the lead levels in blood samples from nielloware workers, to determine airborne lead levels, to describe the workers' hygiene behaviors, and to ascertain and describe any correlations between lead levels in blood samples and lead levels in airborne samples. Methods: Blood samples and airborne samples from 45 nielloware workers were collected from nielloware workplaces in Nakhon Sri Thammarat Province, Thailand. Lead levels were determined by flame atomic absorption spectrometry (FAAS), at a wavelength of 283.3 nm. FAAS was used especially adequate for metals at relatively high concentration levels. Results: The geometric mean of the 45 airborne lead levels was 81.14 μg/m3 (range 9.0-677.2 μg/m3). The geometric mean blood lead level of the 45 workers was 16.25 μg/dL (range 4.59-39.33 μg/dL). No worker had a blood lead level > 60 μg/dL. A statistically significantly positive correlation was found between airborne lead level and blood lead levels (r = 0.747, p < 0.01). It was observed that personal hygiene was poor; workers smoked and did not wash their hands before drinking or eating. It was concluded that these behaviors had a significant correlation with blood lead levels (p < 0.001). Conclusion: Improvements in working conditions and occupational health education are required due to the correlation found between blood leads and airborne lead levels.